2020
DOI: 10.1007/s10140-020-01792-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidentally discovered COVID-19 in low-suspicion patients—a threat to front line health care workers

Abstract: Purpose The COVID-19 pandemic has been responsible for thousands of deaths worldwide. Testing remains at a premium, and criteria for testing remains reserved for those with lower respiratory infection symptoms and/or a known high-risk exposure. The role of imaging in COVID-19 is rapidly evolving; however, few algorithms include imaging criteria, and it is unclear what should be done in low-suspicion patients with positive imaging findings. Methods From 03/01/2020-03/20/2020, a retrospective review of all patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The largest study, a single-center study by Luo et al found that of 1141 confirmed cases of COVID-19, 16% presented with only GI symptoms [ 25 ]. Additionally, many cases of COVID-19 have been found incidentally through abdominal imaging scans indicated by patients presenting mainly or only with GI symptoms [ 20 , 21 , 26 29 ]. Hossain et al found that more than 50% of their 119 patients first demonstrated evidence of COVID-19 incidentally through either an abdominal or cervical spine/neck CT [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest study, a single-center study by Luo et al found that of 1141 confirmed cases of COVID-19, 16% presented with only GI symptoms [ 25 ]. Additionally, many cases of COVID-19 have been found incidentally through abdominal imaging scans indicated by patients presenting mainly or only with GI symptoms [ 20 , 21 , 26 29 ]. Hossain et al found that more than 50% of their 119 patients first demonstrated evidence of COVID-19 incidentally through either an abdominal or cervical spine/neck CT [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three case reports included hematochezia as a symptom [17][18][19]. There are also several case reports that describe patients that present with only GI symptoms initially or throughout the course of their entire infection [20][21][22][23][24]. The largest study, a single-center study by Luo et al found that of 1141 confirmed cases of COVID-19, 16% presented with only GI symptoms [25].…”
Section: Incidental Covid-19 Findings Based On Abdominal Computed Tommentioning
confidence: 99%
“…This should raise concern among clinicians towards close monitoring of patients that test positive for SARS-CoV-2 and have chest imaging findings, as some will eventually become symptomatic. Xiao et al, have reported COVID-19 cases without respiratory symptoms at presentation with incidentally positive chest CT findings, who eventually developed respiratory symptoms warranting critical care and even leading to death 27 ; however, the median age of the patients studied by Xiao et al was 64 years, whereas in the three studies included in the analysis the median ages of patient populations were 31, 32, and 52 years. In the study, all cases that developed symptoms eventually recovered, indicating a good prognosis of this population.…”
Section: Discussionmentioning
confidence: 97%
“…Xiao et al. , have reported COVID-19 cases without respiratory symptoms at presentation with incidentally positive chest CT findings, who eventually developed respiratory symptoms warranting critical care and even leading to death 27 ; however, the median age of the patients studied by Xiao et al. was 64 years, whereas in the three studies included in the analysis the median ages of patient populations were 31, 32, and 52 years.…”
Section: Discussionmentioning
confidence: 97%
“…These results have two important consequences. First, since being asymptomatic was initially considered as a criterion of non-transmission, the high proportion of asymptomatic workers could have played a key role in the evolution of the pandemic acting as disease vectors [8]. Second, the late diagnosis could have aggravated late stages of the disease due to the lack of prompt treatment.…”
Section: Infection Statusmentioning
confidence: 99%